Iraqi Breast Cancer: A Review on Patients’ Demographic Characteristics and Clinico-Pathological Presentation. - Alwan, Nada A. S. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Breast Cancer is the commonest type of malignancy in Iraq. The Iraqi Cancer Registry displays an obvious trend for the disease to affect younger women with advanced stages at the time of presentation. This report presents a review on the main demographic characteristics and clinicopathological parameters in Iraqi patients diagnosed with breast cancer. Patients & Methods: The study was carried out on 721 out of a total of 5044 patients (14.3%) who complained of palpable breast lumps that were diagnosed as cancer. The procedure for tumor nuclear DNA Ploidy assessment was performed by means of Image Cytometry. Immuno-cytochemical and histochemical assays were applied for the determination of Estrogen and Progesterone receptor (ER/PR) contents and Her-2/neu expression of the tumor tissues. Results: Approximately one third of the breast cancer patients were diagnosed in the age period (40- 49 years), 71.9% came from urban areas and 75% were married. History of lactation and hormonal therapy was reported in 63.1% and 29% respectively, while positive family history was recorded in 16.2%. Although the lump was detected by the patient herself in 90.6%, yet only 32% sought medical advice within the first month. Accordingly 47% of these patients presented in advanced stages (III and IV).The main histological type was invasive ductal carcinoma; in which pathological changes of grade II and III were observed in 56.6% and 39.9% respectively. Cytophotometric DNA analysis showed that 80.3% of Iraqi mammary carcinomas were aneuploid. ER and PR positive tumor contents were demonstrated in 65.1% and 45.1% of the examined specimens respectively while Her- 2/neu over expression was displayed in 46.4%. Conclusions: The aforementioned data justifies increasing efforts for establishing comprehensive breast cancer control programs in our country. Further interventional research studies using molecular biomarkers should be promoted to address the factors contributing to the illustrated aggressive tumor behavioral forms